2020
DOI: 10.1038/s41598-020-78029-3
|View full text |Cite
|
Sign up to set email alerts
|

High rate of major drug–drug interactions of lopinavir–ritonavir for COVID-19 treatment

Abstract: The impact of drug–drug interactions (DDI) between ritonavir-boosted lopinavir (LPV-r) to treat patients with coronavirus disease 2019 (COVID-19) and commonly used drugs in clinical practice is not well-known. Thus, we evaluated the rate and severity of DDI between LPV-r for COVID-19 treatment and concomitant medications. This was a cross-sectional study including all individuals diagnosed of SARS-CoV-2 infection treated with LPV-r and attended at a single center in Southern Spain (March 1st to April 30th, 202… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…For example the transport of OATP1B substrate drugs, including statins, repaglinide, olmesartan and valsartan 28,49,50 , or the OCT1-and MATE1-mediated metformin transport 51 could also potentially be affected by LOP and/or RIT. Consistently with in vitro findings of transporter inhibition studies, Macias et al found in a cross-sectional study a high overall frequency of DDI between ritonavir-boosted lopinavir for treating COVID-19 and other relevant medications such as statins, antibiotics, corticosteroids, or antiarrhythmic drugs 52 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For example the transport of OATP1B substrate drugs, including statins, repaglinide, olmesartan and valsartan 28,49,50 , or the OCT1-and MATE1-mediated metformin transport 51 could also potentially be affected by LOP and/or RIT. Consistently with in vitro findings of transporter inhibition studies, Macias et al found in a cross-sectional study a high overall frequency of DDI between ritonavir-boosted lopinavir for treating COVID-19 and other relevant medications such as statins, antibiotics, corticosteroids, or antiarrhythmic drugs 52 .…”
Section: Discussionsupporting
confidence: 55%
“…Consistently with in vitro findings of transporter inhibition studies, Macias et al . found in a cross-sectional study a high overall frequency of DDI between ritonavir-boosted lopinavir for treating COVID-19 and other relevant medications such as statins, antibiotics, corticosteroids, or antiarrhythmic drugs 52 .…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, the dose of CY3A4 substrates should be administered with caution when given in combination with lopinavir/ritonavir. The reported effects of ritonavir on enzymes (CYP 3A, 1A2, 2B6, 2C9, 2C19, and glucuronosyltransferase) may result in lower plasma concentrations of coadministered drugs (respective substrate) or may increase the concentrations of their metabolites (in the case of prodrugs) [27][28][29].…”
Section: Drug-drug Interaction Between Covid-19 Treatments and Antidepressantsmentioning
confidence: 99%
“…Furthermore, lopinavir/ritonavir alters serum lipids to increase the risk of atherosclerosis ( 58 ), which may exacerbate thrombotic events. However, recent reports of arrhythmogenic effects from lopinavir/ritonavir ( 59 , 60 ) and remdesivir ( 61 ) as well as other adverse side effects ( 62 ) may prevent further application in COVID-19 clinical settings. RIC accelerates thrombolysis and decreases platelet-mediated thrombosis in a range of animal models and human patients, while proving safe in a variety of clinical settings ( 63 , 64 ), although the mechanisms underlying the protective effects are not yet determined ( 65 ).…”
Section: Protection Against Covid-19-related Cardiovascular Complicatmentioning
confidence: 99%